Microbial contamination and pharmaceutical stability in space environment: addressing dual challenge with innovative technologies and sustainable practices - Patel, Manali; Patel, Priya; Munshi, Nasreen S.; Patel, Shikha; Patil, Shrushti; Srivastva, Anshu; Dhanraj, Jibin; Duggineni, Raviteja; Mehta, Priti (Frontiers in Space Technologies, 2025)
As human physiology gets altered in the presence of space flight conditions such as microgravity and radiation, microbes also behave differently in space. Many microorganisms have been isolated from space stations and spacecrafts after human space travel. Biofilm formation and biofilm-related fouling specifically in the water recovery system of space stations are known. Microbes have evolved various physiological and genetic adaptations which allow them to grow and develop biofilm in harsh space environments as well. They contaminate the spacecraft environment, its surfaces, water system, and food products and also affect astronauts’ health due to decreased immunity in space. Microbes also develop antibiotic resistance and hence, the choice of antibiotics is a challenging task for treating infection during space travel. There is also a negative impact of the space environment on the stability of antimicrobial agents and many get degraded in the presence of ionizing space radiation. This article describes strategies that may decrease the risk of microbial contamination and associated problems during space expeditions. Various preventive measures are suggested such as use of disinfectants for periodic cleaning, development of antibiotic coated surfaces to kill microbes, development of space-hardy anti-microbial drugs, etc. Multifaceted approach that integrates technological innovation, interdisciplinary collaboration, and robust policy frameworks is essential. Space based microbial research can further help for the innovations in healthcare and environment management on earth.